Cleome burmanii Wight & Arn.-a New Record for Northern India from Gorakhpur - Dixit, S. N.; Siddiqui, M. O. (Indian Forester, 1967)
Cleome burmanii wight and Arn. Is from Carnatic; recently, it has been observed in Gorakhpur, growing luxuriantly along the north-western margin of Ramgarb Tal, which is situtaed in the eastern part of the city.